Results that last : hardwiring behaviors that will take your company to the top - Studer, Quint (J. Wiley & Sons, 2008)
Praise For Results That Last. "Quint Studer is a superb communicator with a deep belief in the power of relationships. His informal tone, sense of humor, and real-world stories bring his business principles to life. Results That Last has a vital, optimistic quality that will keep readers re-reading long after other leadership books have been relegated to a dark corner of the shelf."--Nido Qubein, author of How to Get Anything You Want; President, High Point University; Chairman, Great Harvest Bread Company; and founder, National Speakers Association Foundation. "Results That La